2015
DOI: 10.1002/jcsm.12026
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum phosphorus is associated with catabolic/anabolic imbalance in heart failure

Abstract: BackgroundA higher serum phosphate level is associated with worse outcome. Energy-demanding intracellular transport of phosphate is needed to secure anion bioavailability. In heart failure (HF), energy starvation may modify intracellular and serum levels of phosphate. We analysed determinants of serum phosphates in HF and assessed if catabolic/anabolic balance (CAB) was associated with elevation of serum phosphate.MethodsWe retrospectively reviewed data from 1029 stable patients with HF and have calculated neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…We suppose that hypercatabolism may be an additional mechanism responsible for hyperphosphatemia in severe NS. Similarly, hPi as an effect of increased catabolism has been described by Rozentryt et al in patients with heart failure [27]. It is probable that the same pathogenetic way is associated with hyperuricemia in nephrotic patients.…”
Section: Discussionmentioning
confidence: 52%
“…We suppose that hypercatabolism may be an additional mechanism responsible for hyperphosphatemia in severe NS. Similarly, hPi as an effect of increased catabolism has been described by Rozentryt et al in patients with heart failure [27]. It is probable that the same pathogenetic way is associated with hyperuricemia in nephrotic patients.…”
Section: Discussionmentioning
confidence: 52%
“…The association between 25(OH)D deficiency and higher phosphate concentrations constitutes another argument for this interpretation because, in a CHF patient, the catabolic profile is an independent determinant of phosphate concentration [ 27 ]. Alternatively, the increased phosphate concentration may be a reflection of relative hypoparathyroidism and resulting reduced phosphaturia.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that a catabolic/anabolic imbalance, N‐terminal pro‐B‐type natriuretic peptide values, serum sodium, kidney function, age, and sex were independent predictors of serum phosphorus. Thus, the authors concluded that metabolic status is an independent determinant of serum phosphorus in heart failure …”
Section: Heart Failurementioning
confidence: 99%